Originalism and the Second Amendment: A reassessment. Issue 1 (2nd January 2022) - Smith, Craig R.
ABSTRACT: This article argues that the precept of original meaning is a valid hermeneutic method employed by both the majority and minority in the Supreme Court's ruling in District of Columbia v. Heller, a landmark decision that diminishes the precedents preceding it. After tracing the evolution of the precept of original meaning back to James Madison, who wrote the Second Amendment, this article demonstrates that the precept is widely used as an interpretive method by constitutional scholars and conservative and liberal members of the Supreme Court. Furthermore, embracing original meaning as a hermeneutic method requires the careful consideration of historic context to achieve a proper reading of the text at hand. This article examines the majority opinion and the two dissents in Heller to show how each of these justices used the historic context of the Second Amendment to construct its original meaning. The article then re-examines the context of the Second Amendment to determine its most relevant historiography as a basis for assessing the Supreme Court's reading of the amendment. It concludes that the most sensible reading of the amendment would return to the unanimous Miller precedent of 1939 and allow the banning of certain weapons by states and localities.